Melatonin improves cardiovascular function and ameliorates renal, cardiac and cerebral damage in rats with renovascular hypertension - (:unkn) unknown (WILEY-BLACKWELL, 2009)
The effect of melatonin was investigated in an angiotensin II-dependent renovascular hypertension model in Wistar albino rats by placing a renal artery clip (two-kidney, one-clip; 2K1C), while sham rats did not have clip placement. Starting either on the operation day or 3 wk after the operation, the rats received melatonin (10 mg/kg/day) or vehicle for the following 6 wk. At the end of the nineth week, after blood pressure (BP) and echocardiographic recordings were obtained, plasma samples were obtained to assay lactate dehydrogenase (LDH), creatine kinase (CK), antioxidant capacity (AOC), asymmetric dimethylarginine (ADMA), and nitric oxide (NOx) levels. In the kidney, heart and brain tissues, malondialdehyde (MDA) and glutathione (GSH) levels, superoxide dismutase (SOD), catalase (CAT), myeloperoxidase (MPO) and Na+-K+ ATPase activities were determined. 2K1C caused an increase in BP and left ventricular (LV) dysfunction. In hypertensive animals LDH, CK, ADMA levels were increased in plasma with a concomitant reduction in AOC and NOx. Moreover, hypertension caused a significant decrease in tissue SOD, CAT, and Na+, K+-ATPase activities and glutathione content, while MDA levels and MPO activity were increased in all studied tissues. On the other hand, both melatonin regimens significantly reduced BP, alleviated oxidative injury and improved LV function. In conclusion, melatonin protected against renovascular hypertension-induced tissue damage and improved cardiac function presumably due to both its direct antioxidant and receptor-dependent actions, suggesting that melatonin may be of therapeutic use in preventing oxidative stress due to hypertension.
Keywords: asymmetric dimethylarginine; hypertension; melatonin; oxidative stress; VASCULAR SUPEROXIDE-PRODUCTION; LEFT-VENTRICULAR HYPERTROPHY; CONGESTIVE-HEART-FAILURE; NITRIC-OXIDE SYNTHASE; TARGET ORGAN DAMAGE; ANGIOTENSIN-II; OXIDATIVE STRESS; BLOOD-PRESSURE; ASYMMETRIC DIMETHYLARGININE; MYELOPEROXIDASE ACTIVITY